Ascidiidae Herdman, 1882 (Tunicata: Ascidiacea) on the Pacific coast of Panama - Bonnet, Nadia Y.k.; Rocha, Rosana M.; Carman, Mary R. (Zootaxa, 2013)
The ascidian fauna of the Pacific coast of Panama is poorly known and only recently four species in the family Ascidiidae were reported on. Ascidia is the only known genus of Ascidiidae in Pacific Panama waters. In the present research, we describe a new species, Ascidia sideralis sp. nov., and we document the new occurrence of A. cf. gemmata and A. cf. liberata (both previously known to the West Pacific), A. archaia (a cosmopolitan species elsewhere in the Pacific), A. ceratodes (previously documented in the eastern N. Pacific), and A. sydneiensis (an Atlantic species on the east coast of Panama) in Pacific Panama waters. A tabular key for the identification of Ascidiidae on the American Pacific coast complements this study.